Green synthesis of nanostructured 1T/2H-MoS2 hybrid phase with polyol solvents and microwave heating - Nguyen, Thi Minh Nguyet; Vuong Vinh Dat,; Nguyen Huu Huy Phuc,; Le Van Thang, (Vietnam Journal of Science and Technology, 2024)
Green synthesis approaches have attracted greatly of attention in recent years since they address the issues associated with sustainability than conventional synthesis methods. New research fields in green nanoscience are being developed as a result of the incorporation of green chemistry principles into nanoscience. In this paper, the successful microwave-assisted green synthesis of MoS2 nanoparticles in a single pot using polyol solvents such as ethylene glycol and glycerol is demonstrated. The coexistence of 1T and 2H phases in MoS2 nanomaterials was determined using advanced techniques such as XRD, Raman, XPS, and TEM images. The highest 1T proportion obtained was 84.5% when compared to the 2H phase. The reaction mechanism and the phase transition between 1T and 2H were described and illustrated. The role of polyol solvents in the practical synthesis of nano MoS2 under microwave heating is also evaluated and explained. Due to the ability of the metallic 1T phase to enhance electrical conductivity, it is believed that hybrid nanostructures exhibit superior electrochemical performance for energy storage and conversion applications.